Students’ Problems in Answering Reading Comprehension Question of Descriptive Text in The “Mandiri” Textbook Published by Erlangga at SMPN 1 Kepahiang - Meri Diana; Syahrial Syahrial; Wisma Yunita (Jadila: Journal of Development and Innovation in Language and Literature Education, 2020)
This research aimed to find out the students’ problems in answering reading comprehension questions of descriptive text in the “Mandiri” textbook published and the causes of students’ problems in answering reading comprehension questions of descriptive text in the “Mandiri” textbook published by Erlangga at SMPN 1 Kepahiang. The design of this research was a descriptive quantitative research. This research was designed based on the problems identified and arranged to adjust the main purpose of the research, so that the researcher employed descriptive method. The researcher took 50 students as the sample of this research. The instruments of this study were reading test and interview guideline. The researcher used a reading test in multiple choice forms consisted of fourty numbers of questions included in Mandiri textbook published by Erlangga. Another instrument was an interview guideline. The interview guideline was arranged based on the result of the reading test to reconfirm the result of the reading test and to get an indepth data on the causes of students’ difficulties in reading comprehension. The findings of this research were; (1) the students’ problems in answering reading comprehension questions of descriptive text in the “Mandiri” textbook published by Erlangga at SMPN 1 Kepahiang were finding main idea, identifying specific information, inference, and vocabulary; (2) there were four causes of students’ problems in answering reading comprehension questions of descriptive text in the “Mandiri” textbook published by Erlangga at SMPN 1 Kepahiang; (a) finding main idea is rather complicated, the students need to read the text repeatly to find the main idea; (b) the students need to read from the beginning to finish this description so that they can get the information and answer the questions given; (c) to find inferences they must know the text well and clearly; (d) There are some words that they find difficult to understand and they have never met. They answered that there are some words which are not familiar to them.